The Ways of Psychological and Pedagogical Barriers Overcoming between Teachers and Students during COVID-19 Pandemic - Khudov, Hennadii; Tyurina, Valentina; Ovod, Yuliia; Kozyr, Marharyta; Chala, Anna; Khizhnyak, Irina (My University, 2020)
The COVID-19 pandemic has affected teaching and learning around the world. As a result, schools and higher learning institutions use the e-learning platform to replace face-to-face teaching and learning. E-learning presents new challenges when compared to a traditional classroom because students are separated from their instructor by a computer screen. It has been established that the psychological and pedagogical barrier is an obstacle arising for a teacher in the process of his professional activity, which reduces its effectiveness. The main psychological and pedagogical barriers are highlighted, which are combined into groups: due to the personal and professional qualities of the teacher; caused by the physical and psychological characteristics of the student himself; determined by the specifics of the subject of interaction; caused by unfavorable factors of the social and material environment in which educational interaction takes place. An in-depth analysis of typical barriers that potentially arise between a teacher and students makes it possible to determine ways to overcome them. A psychological portrait of a personality that potentially creates barriers in interpersonal interaction is outlined. The paper proposes the ways of overcoming psychological and educational barriers between teachers and students during the COVID-19 pandemic.
KHUDOV Hennadii.The ways of psychological and pedagogical barriers overcoming between teachers and students during Covid-19 pandemic / Hennadii KHUDOV, Valentina TYURINA, Yuliia OVOD, Marharyta KOZYR, Anna CHALA, Irina KHIZHNYAK // Sys Rev Pharm : A multifaceted review journal in the field of pharmac. - 2020. - № 11(11). - Р. 373–379.
Keywords: COVID-19, пандемія, вчитель, студент, психолого-педагогічний бар’єр, подолання, електронне навчання; COVID-19, pandemic, teacher, student, psychological and pedagogical barrier, overcoming, e-learning; COVID-19, пандемия, учитель, студент, психолого-педагогический барьер, преодоление, электронное обучение